Organophosphate Insecticide Exposure Impacts Reproductive Success in Insensitive Acetylcholinesterase Anopheles gambiae Mosquitoes - Medjigbodo, Adandé A.; Djihinto, Oswald Y.; Salavi, Esther B. J.; Sonounameto, Eric G.; Abbey, Emmanuella; Djossou, Laurette; Djogbénou, Luc S. (Frontiers in Tropical Diseases, 2022)
Extensive use of insecticides has led to the selection of resistance alleles in malaria vectors threatening the control programs. Even if mosquitoes are not killed directly in the contact of insecticide-treated bed nets, their capacity to transmit malaria parasite could be decreased because of the consequences on their life-history traits after repeated exposure. The current work investigated the effects of organochlorine, carbamate, organophosphate, and pyrethroid insecticide exposure on the reproductive success in Anopheles gambiae s.s. Two Anopheles gambiae strains, AcerKis, KisKdr, were used. According to WHO recommendations, female mosquitoes of these resistant strains were exposed to discriminant doses of DDT, chlorpyriphos-methyl, bendiocarb, and permethrin insecticides. Surviving mosquitoes were then fed and allowed to lay eggs. Fecundity was assessed by examining the number of eggs per mosquito, the number of larvae per egg batch and larval hatching rates were used to evaluate the fertility. The data showed that AcerKis females surviving chlorpyriphos-methyl exposure significantly laid few eggs. No significant difference in the hatching rate was noticed in AcerKis females exposed to bendiocarb compared to their control. No significant effect on the fecundity and fertility was observed in KisKdr females exposed to permethrin. Our finding showed that organophosphate insecticides represented here by chlorpyriphos-methyl could hamper egg-laying in insensitive acetylcholinesterase An. gambiae female mosquitoes. This knowledge could help design alternative vector control strategies targeting fecundity and fertility in resistant malaria vectors.